Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(2x-1\right)^6=\left(2x-1\right)^8\Leftrightarrow\left(2x-1\right)^6=\left(2x-1\right)^6.\left(2x-1\right)^2\)
\(\Rightarrow\orbr{\begin{cases}\left(2x-1\right)^6=0\\\left(2x-1\right)^2=1\end{cases}}\)
Suy ra:
\(2x-1=0\Rightarrow2x=1\Rightarrow x=\frac{1}{2}\)
Hoặc \(2x-1=1\Rightarrow2x=2\Rightarrow x=1\)
Hoặc \(2x-1=-1\Rightarrow2x=0\Rightarrow x=0\)
Vậy có 3 giá trị x thỏa mãn là 0;1/2;1
\(\left(2x+1\right)^4=\left(2x+1\right)^6\)
\(\left(2x+1\right)^4-\left(2x+1\right)^6=0\)
\(\left(2x+1\right)^4\left[1-\left(2x+1\right)^2\right]=0\)
\(\hept{\begin{cases}\left(2x+1\right)^4=0\\1-\left(2x+1\right)^2=0\end{cases}}\)
\(\hept{\begin{cases}2x+1=0\\\left(2x+1\right)^2=1\end{cases}}\)
\(\hept{\begin{cases}2x+1=0\\2x+1=1\end{cases}}\)
\(\hept{\begin{cases}x=-\frac{1}{2}\\x=0\end{cases}}\)
=.= hok tốt!!
(2x-1)6 = (2x-1)8
=> 2x-1 \(\in\){-1; 0; 1}
=> 2x \(\in\){0; 1; 2}
=> x \(\in\){0; 1/2; 1}
Vì \(\left(2x-1\right)^6;\left(2x-1\right)^8\ge0,\forall x\)
\(\Rightarrow\left(2x-1\right)^6=\left(2x-1\right)^8\Leftrightarrow\left(2x-1\right)=0\Leftrightarrow x=\frac{1}{2}\)
(2x - 1)6 = (2x - 1)8
=> (2x - 1)8 - (2x - 1)6 = 0
=> (2x - 1)6.[(2x - 1)2 - 1] = 0
=> \(\orbr{\begin{cases}\left(2x-1\right)^6=0\\\left(2x-1\right)^2-1=0\end{cases}}\)=> \(\orbr{\begin{cases}2x-1=0\\\left(2x-1\right)^2=1\end{cases}}\)=> \(\orbr{\begin{cases}2x=1\\2x-1\in\left\{1;-1\right\}\end{cases}}\)=> \(\orbr{\begin{cases}x=\frac{1}{2}\\2x\in\left\{2;0\right\}\end{cases}}\)
=> \(\orbr{\begin{cases}x=\frac{1}{2}\\x\in\left\{1;0\right\}\end{cases}}\)
Vậy \(x\in\left\{\frac{1}{2};1;0\right\}\)
\(\left(2x-1\right)^6=\left(2x-1\right)^8\)
=>\(\left(2x-1\right)^6-\left(2x-1\right)^8=0\)
=>\(\left(2x-1\right)^6\left[1-\left(2x-1\right)^2\right]=0\)
=>\(\left(2x-1\right)^6\left(1-2x+1\right)\left(1+2x-1\right)=0\)
=>\(\left(2x-1\right)^6\left(2-2x\right)2x=0\)
=>(2x-1)6=0 hoặc 2-2x=0 hoặc x=0
+)Với (2x-1)2=6 => x=\(\frac{1}{2}\)
+)Với 2-2x=0 => x=1
Vậy \(x\in\left\{0;\frac{1}{2};1\right\}\)
(2x-1)6=(2x-1)8
=>2x-1=0=>2x=1=>x=1/2
2x-1=1=>2x=2=>x=1
Vậy x=1/2
x-1
<=> (2x-1)^8 - (2x-1)^6 = 0 <=> (2x-1)^6 ( (2x-1)^2 -1) = 0 <=>\(\orbr{\begin{cases}\left(2x-1\right)^6\\\left(\left(2x-1^2\right)-1\right)=0\end{cases}\Leftrightarrow\orbr{\begin{cases}2x-1=0\\\left(2x-1\right)^2=1\Leftrightarrow\end{cases}}\orbr{\begin{cases}x=\frac{1}{2}\\\orbr{\begin{cases}2x=2\\2x=0\end{cases}}\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=\frac{1}{2}\\\orbr{\begin{cases}x=1\\x=0\end{cases}}\end{cases}}}\)
Vậy x thuộc {1/2; 1; 0}
(2x - 1)6 = (2x - 1)8
(2x - 1)6 = (2x - 1)6 . (2x - 1)2
=> (2x - 1)2 = 1
=> \(\hept{\begin{cases}2x-1=1\\2x-1=-1\end{cases}\Rightarrow\hept{\begin{cases}x=1\\x=0\end{cases}}}\)
\(\left(2x-1\right)^6=\left(2x-1\right)^8\)
\(\Rightarrow TH1:\) \(2x-1=1\Rightarrow2x=2\Rightarrow x=1\)
\(TH2:\) \(2x-1=-1\Rightarrow2x=0\Rightarrow x=0\)
\(TH3:\) \(2x-1=0\Rightarrow2x=1\Rightarrow x=\frac{1}{2}\)
Vậy: \(x=1\) hoặc \(x=0\) hoặc \(x=\frac{1}{2}\)